Actinoplanes flavus sp. nov., a novel cellulase-producing actinobacterium isolated from coconut palm rhizosphere soil. Issue 9 (9th September 2021) - Luo, Xianxian; Sun, Xiujun; Huang, Zhenzhen; He, Chuan; Zhao, Junwei; Xiang, Wensheng; Song, Jia; Wang, Xiangjing
Abstract : A novel cellulase-producing actinomycete, designated strain NEAU-H7 T, was isolated from coconut palm rhizosphere soil collected from Wenchang City, Hainan Province, PR China. A polyphasic taxonomic study was carried out to establish the status of this strain. Results of 16S rRNA gene sequence analysis indicated that strain NEAU-H7 T belonged to the genus Actinoplanes, with highest similarity to Actinoplanes hulinensis NEAU-M9 T (99.2 % 16S rRNA gene sequence similarity). The diagnostic sugars in cell hydrolysates were determined to be ribose, galactose and mannose. The major fatty acids (>10%) were C16 : 0, C18 : 1 ω 9 c and C18 : 0 . The predominant menaquinones were identified as MK-9(H4 ) and MK-9(H6 ). The major polar lipids were phosphatidylethanolamine, phosphatidylinositol and two phosphatidylinositol mannosides. The amino acid of the cell-wall peptidoglycan was determined to be meso -diaminopimelic acid. The DNA G+C content was 71.2 mol%. Phylogenetic analysis using 16S rRNA gene sequences showed that strain NEAU-H7 T formed a stable phyletic line with A. hulinensis NEAU-M9 T . However, whole-genome phylogeny showed strain NEAU-H7 T formed a stable phyletic line with A. hulinensis NEAU-M9 T (99.2%), Actinoplanes campanulatus DSM 43148 T (98.6%), Actinoplanes capillaceus DSM 44859 T (98.3%) and Actinoplanes lobatus DSM 43150 T (97.6%). The digital DNA–DNA hybridization (dDDH) results between them were 53.6 (50.9–56.2), 54.1 (51.3–56.9), 53.1 (50.3–55.9) and 52.9 % (50.1–55.6 %), and whole-genome average nucleotide identity (ANI) values between them were 93.7, 93.6, 93.5 and 93.5 %. The low dDDH and ANI values demonstrated that strain NEAU-H7 T could be distinguished from its reference strains. Moreover, genomic analysis indicated that the strain NEAU-H7 T had the potential to decompose cellulose and produce bioactive compounds. On the basis of morphological, chemotaxonomic and phylogenetic characteristics, strain NEAU-H7 T is proposed to represent a novel species of the genus Actinoplanes, with the name Actinoplanes flavus sp. nov. The type strain is NEAU-H7 T (=CCTCC AA 2020034 T =DSM 112042 T ).